PENGARUH NILAI PELANGGAN DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN KEDAI KOPI BANYUATIS DI KECAMATAN DENPASAR TIMUR - Negara, I Kadek Masami; Wijaya, Bagus Arya (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Ngurah Rai, 2024)
The objective of this study is to investigate the interplay between customer value and customer satisfaction, customer value and customer loyalty, and customer loyalty. The research methodology employed in this study is causal quantitative in nature. All participants in this study are patrons of Kedai Kopi Banyuatis. The focal points of this study revolve around the following variables: customer value, customer satisfaction, and customer loyalty. One hundred illustrations were utilized in this study. Data is compiled through the use of a questionnaire and subsequently subjected to route analysis for analysis. The findings of this study demonstrate the following: (1) customer value and customer satisfaction have a significant and positive effect on customer loyalty; (2) customer value and customer satisfaction have a significant and positive effect on customer loyalty simultaneously; and (3) customer value and customer satisfaction have a positive and significant effect on customer satisfaction simultaneously.